Landfill Liners Properties Using Pressmud and Modified Marine Clay - Abdul Rahman, Abdul Samad; Safingi, Shafizah; Sidek, Norbaya; Arshad, Mohd Fadzil (International Journal of Integrated Engineering, 2024)
Rapid population growth and changes in lifestyle have resulted in increased solid waste generation, leading to a pressing concern for effective waste disposal. Landfill leachate, containing harmful pollutants, poses a significant environmental risk to landfills. To address this issue, studied was conducted to assess the effectiveness of using pressmud as an absorbent material in landfill liners. The study involved mixing different proportions of pressmud with marine clay and evaluate the physical properties. Results showed that the addition of pressmud significantly increased the compressive strength of the samples. After 7 days of curing, results of the initial Unconfined Compressive Strength (UCS) of the marine clay after curing for 7 days stood at 121.5 kPa. With the additional of 10% pressmud, it rose up to 176.7 kPa and increased to 233.3 kPa with 20% pressmud. The highest was observed in marine clay samples with a pressmud concentration of 20%, where the values rose from 154 kPa at 0 days to 233.3 kPa after 7 days of curing. X-ray Fluorescence (XRF) test analysis revealed that higher concentrations of Calcium oxide, CaO (64.3155%), Magnesium oxide, MgO (2.9759%) and Aluminium oxide, Al2O3 (1.0318%) in pressmud, indicating its potential for adsorbing contaminants due to adsorption properties. In conclusion, the pressmud is a potential substance that can be used as a filter the prevent leaches from landfill to contaminated the soil.